Bimbingan dan Pelatihan Konten Sosial Media pada UKM “Jajanan Bian” Kota Malang untuk Meningkatkan Penjualan - Rizky Kurniawan Murtiyanto; Rizka Rahmawati; Farika Nikmah; Halid Hasan; Tatiana Kristianingsih (ISAS (Indonesian Society of Applied Science), 2025)
Social media nowadays is a marketing tool that supposed to be had by business owners because we can say that almost all people, especially in Indoneisa is social media active users, so if the business owner needs to be able to communicate with the target market or customers, it is highly recommended for them to optimize the use of social media. Though, there is a problem that usually faced by the small and medium enterprises that is lack of human resources and limited skill and knowledge about social media marketing, so by having this program, it is expected that in the future the SME can maximize the use of their social media platforms. The method applied in this activity of community service is doing training and mentoring with the business owner as the one that designs and plans her company marketing strategy. By having all the activities, it is found that the inconsistency in uploading and traditional content writing make the social media communication lack of engagement, so in conclusion finding customers behavior in using social media and creating a more life-connected experience content can create more interest for the custome